2020
DOI: 10.1038/s41598-020-58086-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal genetic tagging of a cosmopolitan planktivorous shark provides insight to gene flow, temporal variation and site-specific re-encounters

Abstract: Migratory movements in response to seasonal resources often influence population structure and dynamics. Yet in mobile marine predators, population genetic consequences of such repetitious behaviour remain inaccessible without comprehensive sampling strategies. Temporal genetic sampling of seasonally recurring aggregations of planktivorous basking sharks, Cetorhinus maximus, in the Northeast Atlantic (NEA) affords an opportunity to resolve individual re-encounters at key sites with population connectivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 87 publications
(91 reference statements)
1
24
0
Order By: Relevance
“…The basking shark Cetorhinus maximus (Rus Hoelzel et al, 2006) and the megamouth shark Megachasma pelagios (Liu et al, 2018) are both characterized by a single, globally distributed population making both of these species less divergent than the whale shark. While recent research has suggested some level of genetic structure for the basking shark in the northeast Atlantic, a single panmictic population remains the prevailing view (Lieber et al, 2020). If correct, the single population model for both the basking and megamouth sharks suggests a clear difference in the recent dispersal patterns of the three planktivorous shark species.…”
Section: Discussionmentioning
confidence: 99%
“…The basking shark Cetorhinus maximus (Rus Hoelzel et al, 2006) and the megamouth shark Megachasma pelagios (Liu et al, 2018) are both characterized by a single, globally distributed population making both of these species less divergent than the whale shark. While recent research has suggested some level of genetic structure for the basking shark in the northeast Atlantic, a single panmictic population remains the prevailing view (Lieber et al, 2020). If correct, the single population model for both the basking and megamouth sharks suggests a clear difference in the recent dispersal patterns of the three planktivorous shark species.…”
Section: Discussionmentioning
confidence: 99%
“…More data on at-sea distribution of basking sharks is required to understand habitat use, threat overlap, and population status throughout the New Zealand and South Pacific region. The total South Pacific basking shark population size is unlikely to be high; in the Northeast Atlantic, basking shark numbers likely do not exceed 10 000 individuals (Lieber et al, 2020). With little population differentiation across global regions, it is plausible that basking sharks observed in New Zealand waters engage in large scale intra-and inter-oceanic migrations (Lieber et al, 2020).…”
Section: Future Directionsmentioning
confidence: 99%
“…The total South Pacific basking shark population size is unlikely to be high; in the Northeast Atlantic, basking shark numbers likely do not exceed 10 000 individuals (Lieber et al, 2020). With little population differentiation across global regions, it is plausible that basking sharks observed in New Zealand waters engage in large scale intra-and inter-oceanic migrations (Lieber et al, 2020). This may make species' detection more difficult in the vast marine space of New Zealand's EEZ.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to their life history (i.e., long lifespan, late maturity, and slow growth) and habitat use, sharks are exposed to pressure coming from different anthropogenic activities and therefore are subject to a higher risk of extinction if compared to other vertebrates (Lieber et al 2020). The main threats are represented by targeted harvesting (Li et al 2012;Cochran et al 2016;Perry et al 2018), bycatch, illegal fishing, habitat modification, vessel strikes (Speed et al 2008), and contaminant exposure (Boldrocchi et al 2020).…”
Section: Introductionmentioning
confidence: 99%